American lion : Andrew Jackson in the White House - Meacham, Jon (Random House, 2008)
A thought-provoking study of Andrew Jackson chronicles the life and career of a self-made man who went on to become a military hero and seventh president of the United States, critically analyzing Jackson's seminal role during a turbulent era in history, the political crises and personal upheaval that surrounded him, and his legacy for the modern presidency.